Job satisfaction and employees performance in a public service; a case study in Employee Provident Fund / Nurul Nadia Najib - Najib, Nurul Nadia (2009)
This study investigate a global measure for job satisfaction on the following four factors; communication, motivation, training and leadership skill. A survey was conducted to investigate either those factors are absolute contribute to the satisfaction of work environment and also their description. The study was administered on 107 workers from every department. Findings were based on the informal responses from all the workers and also from data receive from year of 2008. The findings revealed that almost of the workers are satisfied with their job description and also gave full commitment with the organization. All four factors are related each other in order to improve in productivity and enhancing quality. Findings also could conclude that Employee Provident Fund staff with corporation from management side is using the four factors which are communication, motivation, training, and also leadership skill in order to ensure the job satisfaction from the employees. So there are few conclusion and recommendations for organization to make. Firstly, management need to always encouraging employee’s suggestions on how to be more improving in their task. Next, encouraging two-way communication with the management and also from employees itself in order to identify the needs needed by the employees to make them feel satisfy with the task provided for them. Lastly, provide constructive feedback because with positive feedback, it could create a good performance by both party and beside corporation from members too.